Cocaine politics : drugs, armies, and the CIA in Central America - Scott, Peter Dale (University of California Press, 1998)
When the San Jose Mercury News ran a controversial series of stories in 1996 on the relationship between the CIA, the Contras, and crack, they reignited the issue of the intelligence agency's connections to drug trafficking, initially brought to light during the Vietnam War and then again by the Iran-Contra affair. Broad in scope and extensively documented, Cocaine Politics shows that under the cover of national security and covert operations, the U.S. government has repeatedly collaborated with and protected major international drug traffickers. A new preface discusses developments of the last six years, including the Mercury News stories and the public reaction they provoked. -- Provided by publisher